2012
DOI: 10.1155/2012/737421
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Changes Affect Material Properties and Cell Behavior in HA-Based Hydrogels

Abstract: To develop and optimize new scaffold materials for tissue engineering applications, it is important to understand how changes to the scaffold affect the cells that will interact with that scaffold. In this study, we used a hyaluronic acid- (HA-) based hydrogel as a synthetic extracellular matrix, containing modified HA (CMHA-S), modified gelatin (Gtn-S), and a crosslinker (PEGda). By varying the concentrations of these components, we were able to change the gelation time, enzymatic degradation, and compressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Thiolated carboxymethyl hyaluronic acid (CMHA‐S) was synthesized as previously described . Thiol modification (3 × 10 −4 mmol/mg) was assessed using 5,5′‐dithio‐bis(2‐nitrobenzoic acid) (Ellman's reagent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiolated carboxymethyl hyaluronic acid (CMHA‐S) was synthesized as previously described . Thiol modification (3 × 10 −4 mmol/mg) was assessed using 5,5′‐dithio‐bis(2‐nitrobenzoic acid) (Ellman's reagent).…”
Section: Methodsmentioning
confidence: 99%
“…Thiolated carboxymethyl hyaluronic acid (CMHA-S) was synthesized as previously described. 25 Thiol modification (3 Â 10 À4 mmol/mg) was assessed using 5,5 0 -dithio-bis(2nitrobenzoic acid) (Ellman's reagent). Molecular weight (340 kDa) was assessed using gel permeation chromatography and dynamic light scattering.…”
Section: Crosslinked Cmha-s Hydrogelmentioning
confidence: 99%
“…Similarly, hydrogels with intermediate elasticity were found to significantly increase the secretion of pro-angiogenic factors from adipose-derived stem cells [102]. Unfortunately, increasing hydrogel stiffness and crosslinking density often results in slower hydrogel degradation kinetics [85,103]. With a decrease in hydrogel degradation, there may be an associated decrease in the diffusion of secreted soluble factors, thus limiting the therapeutic benefit of transplanted stem cells [104].…”
Section: Materials Approaches To Address Mechanical Requirements Of Cementioning
confidence: 99%
“…Additionally, the mechanical properties of the scaffolds must be appropriate to support cell proliferation and provide stability to counter cellular contractile forces imposed during migration throughout the matrix . Lawyer et al reported that the stiffness of the scaffolds greatly impacts the migration and proliferation abilities of the cells in the scaffold . Thus, it has been concluded that a synergistic effect exists between the biological and mechanical properties of the scaffold which plays a significant role in determining the physiological behavior of the encapsulated cells.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Lawyer et al reported that the stiffness of the scaffolds greatly impacts the migration and proliferation abilities of the cells in the scaffold. 23 Thus, it has been concluded that a synergistic effect exists between the biological and mechanical properties of the scaffold which plays a significant role in determining the physiological behavior of the encapsulated cells. These properties must be investigated and understood before the scaffold can be implemented in vivo.…”
Section: Introductionmentioning
confidence: 99%